Pengaruh Dukungan Keluarga dan Depresi terhadap Kualitas Hidup Lansia di Panti Wreda Widhi Asih Surakarta - Aranssa Dwiveronikca Rajagukguk; Marjam Desma Rahadhini; Aris Eddy Sarwono (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This study aims to describe the conditions and analyze the influence of family support and depression on the quality of life of the elderly at the Widhi Asih Nursing Home in Surakarta. An elderly person is someone who has entered the age of 60 years and over. The elderly are an age group of humans who have entered the final stages of their life. Family support is an important element to motivate the elderly, increase self-confidence, accompany the elderly in meeting their needs and dealing with their problems. The higher the support received from the family, the quality of life will increase. Depression is a mood disorder that affects an individual's feelings, ability to think and ability to carry out daily activities (playing, sleeping and working). This research is a survey study of 15 elderly people at the Widhi Asih Nursing Home in Surakarta. The types of data used are primary and secondary data. Data collection techniques use questionnaires, observation and literature study. The data analysis technique uses the SEM method with the SmartPLS 3 analysis tool. The results of this study show that family support has a positive and significant effect on the quality of life of the elderly and depression has a negative and significant effect on the quality of life of the elderly.